Meningkatkan Disiplin Belajar Peserta Didik melalui Metode Reward and Punishment dalam Pembelajaran Matematika Kelas 1 SD Kanisius Kotabaru - Fitriana, Reza; Sarkim, Tarsisius (Paedagogie, 2024)
This study aims to improve the learning discipline of students through reward and punishment methods in learning Mathematics grade 1 SD Kanisius Kotabaru Yogyakarta. This type of research is a class action research carried out in two cycles. For each cycle through 4 stages namely planning, action, observation, and reflection. The research model used is the Kemmis-Taggart model. The subjects of this study were grade 1 students of SD Kanisius Kotabaru Yogyakarta totaling 13 students. The object in this study is the learning discipline of learners in Mathematics learning. Data collection techniques use observation, documentation, field notes and interviews. Data analysis techniques use quantitative descriptive statistics. This study used success indicators with an average value of learning discipline, which is 81-100% with a very good category. The results showed that through the reward and punisment method, the learning discipline of grade 1 students of SD Kanisius Kotabaru in learning Mathematics has increased. This can be seen from the results of the pre-cycle percentage of 53.8% with the medium category, in cycle 1 it increased by a percentage of 76.1%, then increased in cycle II to 84.6%. This shows that using reward and punishment can improve student learning discipline.